Information Delivery in Smart Home Automation Through Security Technique - Rasal, Suraj; , Srijan; Kundu, Vaibhav; Labdhi, Linika (International Journal of Computer Sciences and Engineering, 2020)
This project’s motive is to construct a home automation system that uses any mobile device or any electric gadget to control the various home appliances. Smart home automation is very modern and developing field when it uses modern technologies such as Internet of Things (IoT). There are many existing smart home automation systems which includes automatic lights switch on and off, controlling the speed of fan, motion sensors, noise detectors, etc. Most of the electronic appliances which are included in the smart home appliances can be used or manipulated by any user which directly breaches the security of this system. This research mainly deals with the security of the appliances and better performance of the devices installed within the smart home.